Genetic variation in morphological traits in cotton and their roles in increasing phosphorus-use-efficiency in response to low phosphorus availability - Kayoumu, Mirezhatijiang; Li, Xiaotong; Iqbal, Asif; Wang, Xiangru; Gui, Huiping; Qi, Qian; Ruan, Sijia; Guo, Ruishi; Dong, Qiang; Zhang, Xiling; Song, Meizhen (Frontiers in Plant Science, 2022)
Phosphorus (P) is an essential macronutrient required for fundamental processes in plants. Trait plasticity is crucial for plant adaptation to environmental change. Variations in traits underlie diverse phosphorus (P) acquisition strategies among plants. Nevertheless, how the intraspecific plasticity and integration of morphological traits, and contributes to Phosphorus-Use-Efficiency in cotton is unknown. To assess the genetic variability of morphological traits and their relation to phosphorus use efficiency, 25 morphological traits were assessed in 384 cotton genotypes grown with low P (LP, 10mol. L−1) and normal nutrition (CK, 500mol. L−1). Results revealed a large genetic variation in mostly morphological traits under low P. Significant enhancement in root traits, and phosphorus efficiency-related traits like PUE were observed at LP as compared to CK conditions. In response to P availability, cotton genotypes showed large plasticity in shoot and total dry biomass, phosphorus efficiency related traits (i.e. phosphorus/nitrogen use efficiency, phosphorus/nitrogen uptake efficiency), and most root traits, but a limited response in root dry biomass, taproot length, root surface area, root volume, and SPAD value. In addition, significant correlations were observed between PUtE, NUE, TDB, and RTD with PUE, under both P supply level and phosphorus stress index, which may be a key indicator for improving PUE under LP conditions. Most root traits are most affected by genotypes than nutrition level, conserved, the PUE is more affected by the nutrition level than the genotype effect. Principal component analysis depicted the comprehensive indicators under two P supply conditions were mainly reflected in root-related traits and morphological indicators such as dry matter biomass. These results indicate that interspecific variations exist within these cotton genotypes and traits. Our results provide suggestions for future research to enhance the ability of the earth system model to predict how crops respond to environmental interference and provide target quality for cotton breeding in phosphorus-deficient areas.